Scrum product owner : LiveLessons (LiveLessons (Indianapolis, Ind.), 2018)
"Scrum Product Owner LiveLessons helps you as a Product Owner understand your role in the Scrum process. It also provides you with tips and practices that Tommy has learned over the years to help you consistently deliver high quality, valuable products to your customers."--Resource description page